2014
DOI: 10.1038/nature12989
|View full text |Cite
|
Sign up to set email alerts
|

A dedicated circuit links direction-selective retinal ganglion cells to the primary visual cortex

Abstract: How specific features in the environment are represented within the brain is an important unanswered question in neuroscience. A subset of retinal neurons, called direction selective ganglion cells (DSGCs) are specialized for detecting motion along specific axes of the visual field1. Despite extensive study of the retinal circuitry that endows DSGCs with their unique tuning properties2,3, their downstream circuitry in the brain and thus their contribution to visual processing has remained unclear. In mice, sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
269
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 291 publications
(287 citation statements)
references
References 40 publications
16
269
2
Order By: Relevance
“…Previous work (Swadlow and Weyand 1985) showed that LGN DS neurons do project to V1 and that their axons have conduction velocities similar to those of concentric LGN neurons, but the terminal layer of these axons could not be determined with the antidromic methods that were employed. Although our preliminary studies (Hei et al 2013) indicate that at least some LGN DS neurons provide a strong synaptic impact in layer 4, recent work in mouse (Cruz-Martin et al 2014) indicates that LGN DS neurons located in the shell region of the LGN selectively target the superficial layers of V1. Future work will resolve this issue.…”
Section: Discussionmentioning
confidence: 68%
“…Previous work (Swadlow and Weyand 1985) showed that LGN DS neurons do project to V1 and that their axons have conduction velocities similar to those of concentric LGN neurons, but the terminal layer of these axons could not be determined with the antidromic methods that were employed. Although our preliminary studies (Hei et al 2013) indicate that at least some LGN DS neurons provide a strong synaptic impact in layer 4, recent work in mouse (Cruz-Martin et al 2014) indicates that LGN DS neurons located in the shell region of the LGN selectively target the superficial layers of V1. Future work will resolve this issue.…”
Section: Discussionmentioning
confidence: 68%
“…These findings suggest that the orientation selectivity of some dLGN neurons might be transmitted from the retina ). In fact, there is a disynaptic circuit linking DSGCs with the superficial layers of the primary visual cortex (V1), through a specialized subdivision of the dLGN (Cruz-Martin et al 2014), further supporting the notion that the direction and orientation selectivity of some V1 neurons may be influenced by the activities of RGCs.…”
Section: Discussionmentioning
confidence: 78%
“…This is possible because the brain projections from the retina are oscillating at 8-14 Hz with visual and association cortices [50,51], and the oscillating activity ''brings" the brain faculties to the retina within milliseconds. Visual information can reach the cortex through the retinogeniculo-cortical pathway [59], and the rich network of neurons via horizontal cells, amacrine cells, and inner and external plexuses [60,61], which happens through the fast back-and-forth oscillations [48,49]. This is what we have named the pre-existing infrastructure of the visual consciousness space.…”
Section: Our New Theory Of Vision and Brain Oscillationsmentioning
confidence: 99%